Layer‐by‐Layer Assembly: Super Gas Barrier and Fire Resistance of Nanoplatelet/Nanofibril Multilayer Thin Films (Adv. Mater. Interfaces 2/2019). Issue 2 (22nd January 2019) - Qin, Shuang; Pour, Maryam Ghanad; Lazar, Simone; Köklükaya, Oruç; Gerringer, Joseph; Song, Yixuan; Wågberg, Lars; Grunlan, Jaime C.
Abstract : A multilayer nanocoating comprised of cellulose nanofibrils and clay nanoplatelets exhibits a unique combination of high flame resistance, gas barrier, optical clarity, and modulus. This nanocoating provides a low‐cost opportunity for environmentally‐benign packaging and fire protection. More details can be found in article number1801424 by Shuang Qin, Lars Wågberg, Jaime C. Grunlan, and co‐authors.